2007
DOI: 10.2169/internalmedicine.46.6404
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Adrenal Insufficiency Caused by Adult Development of Pituitary Stalk Transection

Abstract: We report the case of a 38-year-old

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 6 publications
2
5
0
1
Order By: Relevance
“…The first one of our cases had low free T4 and normal TSH levels along with response to TRH test. There is one case report similar to ours in the literature (11). The patient had low free T4 and normal TSH levels along with the response to TRH test.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The first one of our cases had low free T4 and normal TSH levels along with response to TRH test. There is one case report similar to ours in the literature (11). The patient had low free T4 and normal TSH levels along with the response to TRH test.…”
Section: Discussionsupporting
confidence: 78%
“…The fixed head of the fetus and breech presentation due to small maternal pelvis induce traction and transection of the pituitary stalk, but rarely brain trauma which may be caused by major events such as traffic accident (9). Some of the patients present with growth retardation due to hypotalamic and pituitary deficiency, others are diagnosed with acute adrenal deficiency (10,11). This syndrome is the most commonly diagnosed in childhood, whereas some of the patients are diagnosed in adulthood (12).…”
Section: Discussionmentioning
confidence: 99%
“…The disease initially manifests as growth-hormone-deficient short stature, followed by subsequent development of sequential insufficiency of several other pituitary hormones, and finally ACTH deficiency in adulthood. 4 Transection of the pituitary stalk occurs mainly during an abnormal delivery, such as breech delivery, but brain trauma rarely occurs. 5 The present case demonstrates sequential impairment of secretion of multiple pituitary hormones and transection of the pituitary stalk.…”
Section: Discussionmentioning
confidence: 99%
“…15 The mechanism responsible for pituitary stalk transection syndrome is still unknown. Although there have been many reports that have suggested that endocrinopathy and transection of the pituitary stalk may have an association with breech delivery, [3][4][5][6][7][8][9][10][11] Triulzi et al reported that only 32% of a study population of 101 patients had a birth history of breech delivery. They concluded that dysgenesis of the mediobasal prosencephalic structures or brain anomaly probably caused endocrinopathy, and that breech delivery may be the result of a midline brain anomaly, rather than the cause.…”
Section: Discussionmentioning
confidence: 99%
“…Those patients are diagnosed with “pituitary stalk transection syndrome”. In most cases, GH insufficiency develops first, followed by insufficiencies of gonadotropins and thyroid stimulating hormone (TSH) during childhood, and finally adrenocorticotropic hormone (ACTH) insufficiency in later adulthood (2,3). They also have a potential risk of secondary adrenal insufficiency (2).…”
Section: Introductionmentioning
confidence: 99%